Degradation mechanisms of Microcystin-LR during UV-B photolysis and UV/H2O2 processes: Byproducts and pathways. (October 2017) - Moon, Bo-Ram; Kim, Tae-Kyoung; Kim, Moon-Kyung; Choi, Jaewon; Zoh, Kyung-Duk
Abstract: The removal and degradation pathways of microcystin-LR (MC-LR, [M+H] +  = 995.6) in UV-B photolysis and UV-B/H2 O2 processes were examined using liquid chromatography-tandem mass spectrometry. The UV/H2 O2 process was more efficient than UV-B photolysis for MC-LR removal. Eight by-products were newly identified in the UV-B photolysis ([M+H] +  = 414.3, 417.3, 709.6, 428.9, 608.6, 847.5, 807.4, and 823.6), and eleven by-products were identified in the UV-B/H2 O2 process ([M+H] +  = 707.4, 414.7, 429.3, 445.3, 608.6, 1052.0, 313.4, 823.6, 357.3, 245.2, and 805.7). Most of the MC-LR by-products had lower [M+H] + values than the MC-LR itself during both processes, except for the [M+H] + value of 1052.0 during UV-B photolysis. Based on identified by-products and peak area patterns, we proposed potential degradation pathways during the two processes. Bond cleavage and intramolecular electron rearrangement by electron pair in the nitrogen atom were the major reactions during UV-B photolysis and UV-B/H2 O2 processes, and hydroxylation by OH radical and the adduct formation reaction between the produced by-products were identified as additional pathways during the UV-B/H2 O2 process. Meanwhile, the degradation by-products identified from MC-LR during UV-B/H2 O2 process can be further degraded by increasing H2 O2 dose. Graphical abstract: Highlights: UV-B/H2 O2 process effectively removed microcystin-LR (MC-LR) in water. Eight byproducts were newly identified during UV photolysis of MC-LR. Eleven byproducts were newly confirmed during UV/H2 O2 process of MC-LR. Byproducts during UV/H2 O2 process were further degraded with increasing H2 O2 dose. Degradation pathways of UV photolysis and UV/H2 O2 processes were proposed.